2002
DOI: 10.1128/jcm.40.02.376-381.2002
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-Linked Immunosorbent Assay Specific to Dengue Virus Type 1 Nonstructural Protein NS1 Reveals Circulation of the Antigen in the Blood during the Acute Phase of Disease in Patients Experiencing Primary or Secondary Infections

Abstract: In most conflicts there is the potential that there will be Captured Persons (CPERS) whose medical care is the responsibility of the capturing army. The standard of this care should be to the same standard as that afforded to one's own troops. However the medical practicalities of maintaining such standards can be difficult. This article reviews the practicalities of the medical care of CPERS as part of the UK deployment in Afghanistan on Operation HERRICK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
467
1
18

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 582 publications
(511 citation statements)
references
References 31 publications
25
467
1
18
Order By: Relevance
“…Later studies further demonstrated the presence of dengue NS1 antigen in acute-phase sera of infected individuals. In cultures, the levels of NS1 protein correlated with infectious titers of DENV (Young et al 2000, Alcon et al 2002.…”
Section: Vector-borne and Zoonotic Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Later studies further demonstrated the presence of dengue NS1 antigen in acute-phase sera of infected individuals. In cultures, the levels of NS1 protein correlated with infectious titers of DENV (Young et al 2000, Alcon et al 2002.…”
Section: Vector-borne and Zoonotic Diseasesmentioning
confidence: 99%
“…The antibody assays ideally require appropriately timed paired serum samples for the confirmation of an acute dengue infection (Pan American Health Organization 1994, Guzman and Kouri 1996, Vorndam and Kuno 1997. Over the past decade, several studies (Young et al 2000, Huang et al 2001, Alcon et al 2002, Koraka et al 2003, Xu et al 2006 have shown that detecting dengue nonstructural 1 (NS1) protein could be a promising and effective alternative for the early diagnosis of dengue.…”
mentioning
confidence: 99%
“…As MAC-ELISA has low sensitivity in first 4 -5 days of onset of fever 21 , detection of dengue specific IgA using ICT might be a helpful diagnostic tool in suspected dengue cases. In present study significant proportion of patients (80.5%) were found to be IgA positive within 5 days of onset of illness.…”
Section: -416mentioning
confidence: 99%
“…It accumulates in late endosomes of cultured liver cells where it is quite resistant to degradation; remarkably, DV NS1 pretreatment also appears to enhance DV replication (16). Copious amounts of NS1 circulate in DVinfected patients (17,18) in whom NS1 blood levels have been shown to correlate with disease severity (19). Microvascular leakage in such patients has been linked to complement activation by NS1-antibody complexes (20).…”
mentioning
confidence: 99%